Distribution of Antillesoma (Stephen & Edmonds, 1972) (Sipuncula, Antillesomatidae) in the Southwest Atlantic: New Records and Morphological Notes - Franco, Letícia C.; Kawauchi, Gisele Y. (Zootaxa, 2025)
Sipuncula, a marine annelid group, remains poorly known, particularly in the Southwestern Atlantic. This study focuses on the family Antillesomatidae (Kawauchi, Sharma, & Giribet 2012) and the cosmopolitan species Antillesoma antillarum (Grube & Öersted 1858) to enhance our understanding of its distribution, morphology, and population-level variations. We document A. antillarum at thirteen localities in the Southwestern Atlantic, extending its known range. This work was enabled by reviewing specimens from Brazilian scientific collections, which previously lacked formal records. Detailed morphological analysis and examination of population variations reveal the species’ morphological plasticity and refine its distribution limits. Our findings improve the taxonomic framework for A. antillarum and significantly advance the understanding of Sipuncula diversity and distribution in the region, providing new insights into distribution patterns.